A Study of Feminism in the Novels of Mulkraj Anand and Arundhati Roy (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The majority of novelists in India's early nineteenth-century literary scene were male. The early English novels produced in India, even by male writers, portray a social reality that differs greatly from women since these men saw society and the people's predicament through their own lens. In search of their own unique voices, several female Indian authors have delved into female subjectivity. All of the main characters aspired to break free of the conventional gender norms and find their own unique identities. Because of this, Indian English novels now depict society quite differently. One that goes against the grain of societal consensus. The study's overarching goal is to catalogue the female undercurrents present in TGST and untouchable, a work of postmodern Indian fiction. Novelist and social activist Mulk Raj Anand has written extensively on women's oppression. Millions of Indian women suffer from unsympathetic husbands, cunning in-laws, blasé and censorious relatives, and most of all, crippling guilt and self-blame brought on by centuries of psychological oppression and bombardment. Mulk Raj Anand bravely stands by these women in his novel. Upon finishing this paper, women all around the world—on a global, national, and regional scale—may be able to grasp the empowering message of feminism and deconstruct a positive interpretation of their own femininity and womanhood.